Parameter Estimation and Hybrid Lag Synchronization in Hyperchaotic Lü Systems. (30th March 2014) - Wei, Qing; Wang, Zuolei
Abstract : The antiphase and complete lag synchronization of hyperchaotic Lü systems with unknown parameters is investigated. Based on the Lyapunov stability theory, the sufficient conditions for achieving hybrid lag synchronization are derived. The optimized parameter observers are approached analytically via adaptive control approach. Numerical simulation results are presented to verify the effectiveness of the proposed scheme.